When Plain Language Deceives: Frequent but Generic Words and Misleading Sentence Simplicity in a Mobile Phone Advertisement—An Eye‐Tracking and Decision‐Task Study - Stefano Rastelli; Francesca Pagliara; Marianube Pavia (Applied Cognitive Psychology, 2026)
ABSTRACT This study investigates how plain and apparently simple language can mislead readers in online advertising. Using eye‐tracking and a forced‐choice task, we compared an original smartphone advertisement with a revised version. The revision replaced frequent and generic wording with more specific expressions and substituted a declarative verbal clause with a nominalisation, contrary to common plain language heuristics. Readers of the revised version were significantly more accurate and faster in their decisions, regardless of age and education. Eye‐tracking measures showed reduced reading effort across regions of interest, with the strongest reduction for numerical cost information. The results show that deception in advertising is often misattributed to linguistic obscurity, whereas it more commonly arises from fully intelligible but overly plain and generic wording; by contrast, more specific formulations with less frequent words and explicit structure better support informed decisions.